Trichloroacetic acid in the vegetation of polluted and remote areas of both hemispheresFPart I. Its formation, uptake and geographical distribution - Weissflog, Ludwig (2001)
Trichloroacetic acid (TCA; CCl3COOH) is a phytotoxic chemical. Although TCA salts and derivatives were once deployed as herbicides against perennial grasses and weeds, their use has since been banned because of their indiscriminate herbicidal effects on woody plant species. However, TCA can also be formed in the atmosphere. For instance, high-volatile C2-chlorohydrocarbons tetrachloroethene (TECE, C2Cl4) and 1,1,1-trichloroethane (TCE, CCl3CH3) can react to TCA and other substances under oxidative conditions here. Owing to further industrialisation of Southeast Asia, South Africa and South America, a rise can be expected in the use of TECE as solvents in the metal and textile industries of these regions in the southern hemisphere (SH). The increasing emissions of this substance-together with the rise in the atmospheric oxidation potential caused by urban activities, slash and burn agriculture and forest fires in the SH-will result in the increased input/formation of TCA in the vegetation located on the lee side of these emission sources. By means of biomonitoring studies, inputs/formation of TCA related to the climatic conditions were detected at various locations in South America, Africa, and Europe.